Effectiveness of Adaptation and Integration Mechanisms in Prevention of the Dissemination of Ideologies of Extremism and Terrorism among Migrants - Zalyaev, Rustem Ilkhamovich; Efimova, Sabina Rafailevna (International Journal of Criminology and Sociology, 2022)
Nowadays, undoubtedly, one of the severely potential hazards threatening societies due to the migration processes is the spread of extremist ideologies of terrorism among immigrants worldwide. The article analyzes the effectiveness of adaptation and integration mechanisms so as to prevent the spread of ideologies of extremism and terrorism among migrants. This paper illustrates that adaptation and integration mechanisms have significant multifunctional capabilities in preventing the spread of ideologies of extremism and terrorism among migrants. Different approaches to solving migration issues are taken into consideration. It is positively proven that for the prevention of manifestations of the ideologies of extremism as well as terrorism amongst migrants, a particular model of cultural integration is required. Where integration is able to provide a high degree of cultural cohesion, the formation of mutual respect between cultures so that new cultures can integrate into the existing unified culture of the country. As a result, effective mechanisms for the adaptation and integration of migrants in order to prevent the spread of ideologies of extremism and terrorism among migrants are proposed.